2018
DOI: 10.4103/jcd.jcd_291_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anti-Candida activities of the ancient plants Lawsonia inermis and Ziziphus spina christi with antifungal drugs in Candida species isolated from oral cavity

Abstract: Context:Medicinal plants have reportedly fewer side effects, compared to antifungal agents.Aims:This study was designed to compare the anti-Candida activity of two medicinal plants with two routine antifungal agents, used in the clinics, on Candida species isolated from the oral cavity of the liver transplant patients.Subjects and Methods:Anti-Candida activities of ethanol extracts of Lawsonia inermis leaf and Ziziphus spina christi unripe and ripe fruit (collected from south of Iran) versus nystatin and fluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…stem bark showed an antifungal activity against fungal species, including Aspergillus fumigatus, Syncephalastrum racemosum and Geotricum candidum ( Ads et al, 2017 ) besides, the ethanol extracts of the Ziziphus sp. fruits were found to be effective against some Candida species ( Mardani et al, 2018 ). Controversially, another study showed that the petroleum ether, chloroform, methanol, and aqueous extracts of the fruits, leaves, seeds, and stems of Ziziphus sp.…”
Section: Resultsmentioning
confidence: 99%
“…stem bark showed an antifungal activity against fungal species, including Aspergillus fumigatus, Syncephalastrum racemosum and Geotricum candidum ( Ads et al, 2017 ) besides, the ethanol extracts of the Ziziphus sp. fruits were found to be effective against some Candida species ( Mardani et al, 2018 ). Controversially, another study showed that the petroleum ether, chloroform, methanol, and aqueous extracts of the fruits, leaves, seeds, and stems of Ziziphus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Medicinal plants have been used for many years across the world for numerous diseases due to their low toxicity and ease of absorption, compared with synthetic drugs [15]. There are reports regarding the application of medicinal plants in dentistry [16, 17]. In this study, the methanolic, ethanolic, and aqueous extracts of P. granatum were compared because the type of extract is important in the different properties of the plants.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological studies on Lawsonia inermis revealed antibacterial activity [6,7], antifungal [8,9], antiparasitic [10,11], molluscicidal [12], antioxidant [13,14], hepatoprotective [15,16], central nervous [17], analgesic [18,19], anti-inflammatory [20,21], antipyretic [18], wound [22,23] and burn healing [24], immuno-modulatory [25,26], anti-urolithiatic [27,28], antidiabetic and hypolipidemic [29,30], antiulcer [31], antidiarrhoeal [19] , diuretic [32], anticancer [33,34] and many other pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%